Respostas
respondido por:
0
Resposta:
a) - 8
b) p ( - x ) = - 3 x ³ - x² - 3 x - 6
Explicação passo-a-passo:
Enunciado:
Dado o polinômio p(x) = 3x³ - x² + 3x - 6. Calcule:
a) p(0) + 2p(1)
b) p(-x)
Resolução :
a) p(0) + 2p(1)
p( 0 ) = 3 * 0³ - 0² + 3* 0 - 6
p ( 0 ) = - 6
2 p ( 1 ) = 2 * ( 3 * 1³ - 1² + 3 *1 - 6 )
2 p ( 1 ) = 2 * ( 3 - 1 + 3 - 6 ) ( repare que 3+3 = 6 e 6 - 6 = 0 )
2 p ( 1 ) = 2 * ( - 1 )
2 p ( 1 ) = - 2
p ( 0 ) + 2 p ( 1 ) = - 6 + ( - 2 )
p ( 0 ) + 2 p ( 1 ) = - 8
b) p ( - x )
p ( - x ) = 3 * ( - x )³ - ( - x )² + 3 ( - x ) - 6
p ( - x ) = - 3 x ³ - x² - 3 x - 6
Bom estudo .
---------------------------------
Sinais : ( * ) multiplicação
Perguntas similares
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás